Fermented Astragalus membranaceus could promote the liver and intestinal health of juvenile tiger grouper (Epinephelus fuscoguttatus) - Yang, Jingru; Zhou, Shengjie; Fu, Zhengyi; Xiao, Bo; Li, Minghao; Yu, Gang; Ma, Zhenhua; Zong, Humin (Frontiers in Physiology, 2023)
This study evaluates the effects of different levels of fermented Astragalus (FAM) on liver and intestinal tissue structure, digestive enzyme, serum biochemical parameters and intestinal microbiota structure of tiger grouper (Epinephelus fuscoguttatus). Fish were fed with diets with five levels of FAM (L1:0.25%, L2: 0.5%, L3: 1%, L4: 2% and L5: 4%) in the experimental groups and a regular diet was used as the control (L0: 0%) for 8 weeks. Compared with the crude drug AM, the protein content of FAM was significantly changed by 34.70%, indicating that a large amount of bacterial protein was produced after fermentation, and its nutritional value was improved. FAM significantly effected the growth performance of tiger grouper (P < 0.05), and the weight gain rate (WGR) and specific growth rate (SGR) were highest in L4 group, which were 105.00±7.10% and 1.28±0.06%•d−1 , respectively, while the feed conversion ratio (FC) inL3 and L4 groups was lowest, which were 0.93±0.03 and 0.93±0.07, respectively (P < 0.05). The high density lipoprotein cholesterol (HDL-C) was highest in L4 group (5.53±0.42mmol•L−1 ), being significantly different from L0 group (4.61±0.16 mmol•L−1 ). The area and diameter of hepatocyte were lowest in L3 and L4, which were 48.16±8.74um 2 /7.95±0.54um and 47.98±11.57um 2 /7.75±0.67um, respectively, the density of hepatocyte was highest in L4 group (4590.92±220.97/mm2 ) and relatively decreased in L5 group (3653.75±275.12/mm2). The mucosal height and muscularis thickness were highest in L3 group, which were 447.79±252.91um and 154.85±63.44um, respectively. The intestinal microbiota structure of tiger grouper was changed under the intervention of FAM. The lower abundance of potential pathogenic bacteria and higher abundance of probiotics colonization in L4 group showed that the dose of FAM had the best effect on improving the health of intestinal microbiota. This study indicates that the addition of FAM in the feed contributes to liver health, improves the intestinal morphology and regulates the intestinal microbiota of tiger grouper. The addition ratio of 1% -2% is better on intestinal and liver health, and high addition ratio will cause liver damage. Our work will provide reference for the addition and management of FAM in the aquaculture industry.